Testing in serum for human glandular kallikrein 2, and free and total prostate specific antigen in biannual screening for prostate cancer - Becker, C; Piironen, T; Pettersson, K; Hugosson, J; Lilja, H (2003)
Purpose: We investigated the value of serum measurements for glandular kallikrein 2 (hK2), and free (f) and total (t) prostate specific antigen (PSA) in a second round of biannual screening for prostate cancer. Materials and Methods: In 1995 to 1996, 5,853 of 9,811 randomly selected men in Göteborg, Sweden 50 to 66 years old had PSA measurements. Of 660 men 611 with tPSA 3 ng/ml or greater underwent biopsy and 145 had cancer. All were re-invited 2 years later for PSA testing, and 506 of 596 men with tPSA 3 ng/ml or greater underwent biopsy and 113 cancers were detected. We analyzed hK2, tPSA and fPSA in 423 of 453 (93%) men who underwent biopsy in 1997 to 1998 who were also screened in 1995 to 1996. Results: The 99 of 423 (23%) men who underwent biopsy diagnosed with prostate cancer in 1997 to 1998 had significantly different tPSA, percent fPSA and hK2 X tPSA/fPSA compared to the men with negative biopsies from 2 years earlier. The largest area under curve was obtained for hK2 X tPSA/fPSA in serum from 1995 to 1996 and from 1997 to 1998, but the difference was not significant compared to tPSA and percent fPSA. In serum from 1997 to 1998 measurements of hK2 X tPSA/tPSA gave significantly higher specificity than tPSA at 85% sensitivity, and significantly higher specificity than tPSA and percent fPSA at 70% to 75% sensitivity. In addition, levels of hK2 and hK2 X tPSA/fPSA manifested a significantly greater 2-year increase in men with cancer compared to those with benign biopsies. Conclusions: In men with tPSA levels 3. 0 ng/ml or greater who were not diagnosed with cancer during a first round of screening, hK2 measurements enhanced specificity compared to tPSA testing at moderately high sensitivity, and manifested a greater 2-year increase in men with cancer.